2010
DOI: 10.1007/978-3-642-14128-7_33
|View full text |Cite
|
Sign up to set email alerts
|

The Formulator MathML Editor Project: User-Friendly Authoring of Content Markup Documents

Abstract: Implementation of an editing process for Content MathML formulas in common visual style is a real challenge for a software developer who does not really want the user to have to understand the structure of Content MathML in order to edit an expression, since it is expected that users are often not that technically minded. In this paper, we demonstrate how this aim is achieved in the context of the Formulator project and discuss features of this MathML editor, which provides a user with a WYSIWYG editing style … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…There search aims to simplifyLaTeXformulaentryby:1)allowing rendered formulas to be edited directly alongside their associated LaTeX strings, 2) helping build formulas from smaller ones, and 3) providing searchable formula cards with associated names and descriptions. Equation Editor by [4] allows students to constructequationswithGreekletters, exponents,andmathematical symbols.In [5],the authors demonstrated the Formulator project of MathML editor which provides a user with a WYSIWYG editing style while authoring MathML documents with Content or mixed markup. Furthermore, they presented an approach taken to enhance the availability of the MathML editor to end-users, demonstrating an online version of the editor that runs inside a Web browser.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…There search aims to simplifyLaTeXformulaentryby:1)allowing rendered formulas to be edited directly alongside their associated LaTeX strings, 2) helping build formulas from smaller ones, and 3) providing searchable formula cards with associated names and descriptions. Equation Editor by [4] allows students to constructequationswithGreekletters, exponents,andmathematical symbols.In [5],the authors demonstrated the Formulator project of MathML editor which provides a user with a WYSIWYG editing style while authoring MathML documents with Content or mixed markup. Furthermore, they presented an approach taken to enhance the availability of the MathML editor to end-users, demonstrating an online version of the editor that runs inside a Web browser.…”
Section: Review Of Related Literaturementioning
confidence: 99%